Adoption of IT Infrastructure to Enhance The Environmental Sustainability: Case Of Supply Chain Businesses - Saeed Ahmed; Muhammad Zubair Ahmed; Muhammad Zulqarnain Siddiqui; Tauseef Iqbal Khan; Qazi Shahab Azam (Institute of Business Management, 2020)
This paper investigates the effect of the adoption of IT Infrastructure on environmental sustainability. The purpose is to strike a balance between the adoption of IT as Supply Chain enabling tool and environmental sustainability. Many large organizations are directly responsible for creating an imbalance in nature through industrial contamination. However, with the development of Supply Chain, has brought about awareness of pollution hazards that have endangered environment. IT Infrastructure and its proper adoption can offer a viable solution ensuring environmental sustainability. This study focuses on how businesses can improve supply chain with the adoption of IT Infrastructure that will reduce carbon emission other sources of pollution. Qualitative research is conducted to study the impact and results are represented at the end of the research. In the research findings, it is concluded that Horizontal Collaborative network for Supply Chain is the key to sustainability and the role of IT infrastructure is the dominant factor for improving Supply Chain.